Abnormal uterine bleeding in adolescence - three cases of heavy menstrual bleeding (HMB) - Dominika Zajdel; Paula Jankowska (Journal of Education, Health and Sport, 2022)
Heavy menstrual bleeding (HMB) is profuse, acyclic bleeding from the genital tract, with or without clots, usually lasting more than 10 days. They are the most common cause of abnormal uterine bleeding in adolescence. The following are used in the treatment: iron preparations, antifibrinolytic drugs, NSAIDs, estrogen-progestagen therapy or progestagen therapy. In cases where the Hb concentration is <7-8 g/dl, red blood cells preparation should be transfused. In the article we present a description of three cases of patients with heavy menstrual bleeding (HMB) who were treated in the Pediatric Department of the Independent Public Provincial Specialist Hospital in Chełm.